PERANAN AUDIT INTERNAL DALAM MENUNJANG EFEKTIVITAS PENGENDALIAN INTERNAL ATAS BIAYA PRODUKSI AIR MINUM DALAM KEMASAN 240ML PADA PT. AQUA GOLDEN MISSISSIPPI TBK. - Hardiyanto, Arief Tri (JIAFE (Jurnal Ilmiah Akuntansi Fakultas Ekonomi), 2016)
This study shows how the role of internal audit is adequate can play a role in supporting the effectiveness of internal controls over the production cost of bottled water 240ml at PT. Aqua Golden Mississippi Tbk. (Branch Mekarsari). The method used in this research is descriptive statistic by using Spearman Rank correlation coefficient with n = 15 and a significant level of 0.05. Based on the research that has been described, it can be concluded that the respondents in the role of internal audit is adequately provide answers strongly agree and agree amounting to 96.1% of respondents regarding the effectiveness of internal control over production costs by 97.02% answered strongly agree and agree, The role of internal audit in supporting the effectiveness of internal controls over the production cost of bottled water 240ml including a very strong, which is 89.96%. While the remaining 10.04% influenced by other factors not included in the research conducted by the author. Thus it can be said that adequate internal audit was instrumental in supporting the effectiveness of internal controls over the production cost of bottled water 240ml at PT. Aqua Golden Mississippi Tbk. (Branch Mekarsari).Â Keywords: Internal Audit, Internal Control, Cost of Production